Pelatihan Pembuatan Soal Secara Online Terhadap Guru Kelas Dan Guru bidang Study di SDS PKMI Efesus Aek Batu - Rumiris Lumban Gaol; Dewi Anzelina (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
The impact of the COVID-19 pandemic has penetrated the world of education, the central and regional governments have issued policies to conduct distance learning as an effort to prevent the spread of the corona virus transmission in Indonesia. schools and campuses implement policies for teaching and learning activities from a distance or online learning or what is often called online learning. Educators/Teachers must ensure that teaching and learning activities and exams continue even though students are at home, learning innovation is a solution that needs to be designed and implemented by teachers by maximizing existing media such as online media such as google form. Google Form or Google Forms is a facility provided by Google that is useful for helping plan events, create questionnaires, send surveys, create quizzes for students and students and collect information in an easy and efficient way. This form can be linked to a spreadsheet, so that responses from respondents can be displayed and downloaded in spreadsheet (excel) format. The method used in community service is training in the form of training and questions and answers, from this activity the teacher is able to understand well the online question-making training.